2015
DOI: 10.1021/acs.jpcb.5b05768
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serine Conformers by Matrix-Isolation IR Spectroscopy Aided by Near-Infrared Laser-Induced Conformational Change, 2D Correlation Analysis, and Quantum Mechanical Anharmonic Computations

Abstract: The conformers of α-serine were investigated by matrix-isolation IR spectroscopy combined with NIR laser irradiation. This method, aided by 2D correlation analysis, enabled unambiguously grouping the spectral lines to individual conformers. On the basis of comparison of at least nine experimentally observed vibrational transitions of each conformer with empirically scaled (SQM) and anharmonic (GVPT2) computed IR spectra, six conformers were identified. In addition, the presence of at least one more conformer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 82 publications
2
44
0
Order By: Relevance
“…Based on at least 6 band assignments for each species, Tarczay et al 52 identified six serine conformers (I, II, III, IV, VI, VIII) using matrix-isolation IR spectroscopy assisted by NIR laser irradiation and comparison with anharmonic GVPT2 vibrational computations on a hybrid B2PLYP-D3/B3LYP-D3 force field (Table S6) respectively. The theoretical frequencies in Table 4 for which an experimental assignment exists are italicized.…”
Section: Spectroscopic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on at least 6 band assignments for each species, Tarczay et al 52 identified six serine conformers (I, II, III, IV, VI, VIII) using matrix-isolation IR spectroscopy assisted by NIR laser irradiation and comparison with anharmonic GVPT2 vibrational computations on a hybrid B2PLYP-D3/B3LYP-D3 force field (Table S6) respectively. The theoretical frequencies in Table 4 for which an experimental assignment exists are italicized.…”
Section: Spectroscopic Parametersmentioning
confidence: 99%
“…Italicized entries indicate frequencies for which experimental assignments exist. 52 b Computed using a reduced Fermi resonance interaction threshold ϕ > 16 cm −1 . !…”
Section: Spectroscopic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For n-alcohols the set of the { eq j } conformers was re-optimized employing the MPWB1K functional (Zhao et al, 2004) in combination with the 6-31+G(d,p) basis set (Hehre et al, 1972). In the case of serine, B3LYP/6-31++G * * was the method of choice with the objective of establishing a direct comparison with previous calculations (Najbauer et al, 2015). Geometry optimizations and frequency calculations were carried out with the Gaussian 09 package (Frisch et al, 2004).…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…To the best of our knowledge this is the first work dealing with the conformational flexibility of n-heptanol. Najbauer et al (2015) reported the 14 conformers of L-serine with the lowest Gibbs free energies at 0 K, G o 0K , calculated at the B3LYP/6-31++G * * level. Our algorithm found a total of 72 LL conformers, number that was reduced to 60 (listed in the Supplementary Material) after the HL reoptimizations, also at the B3LYP/6-31++G * * level.…”
Section: Benchmarkingmentioning
confidence: 99%